Software project management in practice - Jalote, P. (Addison-Wesley, 2002)
We often hear about software projects that are late, over budget, or unable to satisfy customer needs. Yet some organizations are able to manage project after project successfully with desired results. In this book, Pankaj Jalote looks at one such organization, Infosys Technologies, a highly regarded high-maturity organization, and details the processes it has in place to manage projects. Revealing exactly how Infosys operates, Jalote provides an excellent case study to guide project managers everywhere. The specific Infosys practices described reflect sound management principles and practices. They are also grounded in common sense, and can be incorporated into any organization's software development operation easily. With an actual software project from Infosys used as a running example, the author explains the key aspects of successful project management-from process planning through project monitoring and closure. The practices discussed are also compatible with the widely adopted Capability Maturity Model® (CMM®). In the end, readers will gain a practical framework for systematically improving the planning and execution of any software project. In-depth coverage of the Infosys software project management process includes: Requirement change management Process planning, tailoring, monitoring, and auditing Effort estimation and scheduling Quantitative quality management Risk assessment and control Measurement and tracking planning Project team planning Customer communication Configuration management Reviews Project tracking and closure analysis Milestone analysis Activity level analysis using SPC Defect prevention The process database Many guidelines exist for achieving higher software process maturity. This book shows you how by example. 0201737213B01182002.